New Paradigm on Plant Quarantine System for Protection of Biological Diversity in Indonesia - Arifin Tasrif; Muhammad Taufik; Nazaruddin Nazaruddin (Universitas Gadjah Mada, 2021)
Plant quarantine system becomes an important pillar in the protection of biological diversities from the threat of plant pests and diseases. The implementation of plant quarantine system currently covers prevention of spread of quarantine pests, food safety, food quality, genetic resources and bio-agents, as well as invasive alien species and genetically modified organism. During 2014 to 2018, a total of 232 frequency intercepted of quarantine pests of viruses, bacteria, fungi, nematodes, insects, and weeds have been detected. These pests associated with plant materials from various countries in Asia, Europe, the United States, Australia and Africa that may potentially threaten biological diversities when dispersed within Indonesian territory. Implementation of risk analysis and appropriate level of protection consideration can be clustered in to pre-border, at-border, and post-border activities in order to mitigate the risk of quarantine pests and biosafety monitoring into Indonesian territory. Utilizing advances in pest detection technology in the industrial era 4.0 could provide benefits in the agricultural sectors. Various detection technologies using drones and bio-sensors have contributed in the field of plant protection, especially as pest detection and monitoring tools in the field. Furthermore, the establishment of proficiency certification agency for plant quarantine systems may contribute efficient and effective operations in the near future.